DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON ARTICULATE STORYLINE 3 TO IMPROVE MATHEMATICAL PROBLEM-SOLVING SKILLS AMONG SEVENTH-GRADE STUDENTS AT SMP NEGERI 7 PERCUT SEI TUAN - saputri Saputri; Rusydi Ananda (Prima: Jurnal Pendidikan Matematika, 2026)
This development research produced an interactive learning media based on Articulate Storyline 3 for the social arithmetic material of seventh grade students at SMP Negeri 7 Percut Sei Tuan using the 4D model (Define, Design, Develop, Disseminate). The results showed that the media was very valid with a percentage of 92% from material and media experts, and very practical based on teacher (100%) and student (97.13%) responses. In addition, this media was proven to be effective in improving students' mathematical problem-solving abilities as indicated by an N-Gain value of 0.73 (high category) through an increase in the average score from 35.22 in the pre-test to 65.26 in the post-test. This media was considered easy to operate, interesting, interactive, and able to motivate students to be active in learning so that it could improve students' mathematical problem-solving abilities. Thus, the Articulate Storyline 3 media on social arithmetic material was proven to be valid, practical, and effective in supporting the improvement of mathematical problem-solving, and could be an innovative alternative in improving the quality of enjoyable mathematics learning according to the demands of the 21st century.